Pediatric autoimmune disorders with gastrointestinal expressions: from bench to bedside - Francalanci, Paola; Cafferata, Barbara; Alaggio, Rita; De Angelis, Paola; Diamanti, Antonella; Parente, Paola; Granai, Massimo; Lazzi, Stefano (Pathologica - Journal of the Italian Society of Anatomic Pathology and Diagnostic Cytopathology, 2021)
The gastrointestinal (GI) tract may be involved in systemic autoimmune diseases or may be the target of organ-specific autoimmunity. Autoimmune enteropathy (AIE) is a rare disorder characterized by severe and protracted diarrhea, weight loss from malabsorption and immune-mediated damage to the intestinal mucosa, generally occurring in infants and young children, only rarely in adult. The salient histopathologic features of AIE are most prominent in the small intestine: villous blunting, crypt hyperplasia, mononuclear cell inflammatory expansion of the lamina propria with intraepithelial lymphocytosis, crypt apoptosis and absence of Paneth cells, goblet cells or both. Esophagus, stomach and colon are frequently also involved. Anti-enterocyte antibodies are identified in the majority of cases, and their presence, even if variable, can help confirming the diagnosis. The purpose of this review is to provide an overview of the latest immunological advances in AIE, as well as to offer a practical approach for histological diagnosis for ‘general’ pathologist. The purpose of this review is to provide an overview of the latest immunological advances in AIE, as well as to offer a practical approach for histological diagnosis for ‘general’ pathologist. (read more)